Preservice teachers' views of global citizenship and implications for global citizenship education. (15th March 2019) - Bruce, Judy; North, Chris; FitzPatrick, Jessica
ABSTRACT: Global citizenship (GC) is becoming increasingly significant as a desirable graduate attribute in the context of increasing globalisation and cultural diversity. However, both the means and ends of GC education are influenced by a divergent range of conceptualizations. The aim of this research project was to investigate preservice teachers' understandings of global citizenship, with a particular focus on cultural diversity. Pre-service teachers (PSTs) participated in interviews, and findings indicated that they were uncertain about the idea of global citizenship, sought harmony and a desire for sameness in culturally diverse relationships, and held ethnocentric, paternalistic and salvationist views about the 'Other'. Drawing on these findings, we present a framework incorporating technicist, humanistic and postcritical conceptions as a tool for analysis of GCE approaches, their means and ends.